Using Corporate Social Marketing in the Power Sector: A Case Study on Energy Efficiency - Saraiva, Andrea; Pinto, Patrícia; Agapito, Dora (Journal of Tourism, Sustainability and Well-being, 2015)
This research was conducted both in Portugal and Brazil and explores energy efficiency (EE) behavioral change programs implemented by a non-state-owned company selling electricity to residential consumers in both markets. In order to understand to what extent the corporate social marketing (CSM) framework is being used in these programs, the motivations of non-state-owned companies to implement EE programs and the approach underpinning these projects are analyzed. Furthermore, this study compares the approaches used by the multinational company in its EE programs implemented in the Portuguese and the Brazilian markets. Data collected from interviews are submitted to comparisons, using the grounded theory. The perspectives of competing companies with similar programs, and other stakeholders are included in the analysis. The research seeks for a substantive theory emerged from the data suitable for the analyzed context. The findings of this predominantly qualitative study suggest that the corporate social marketing approach contributes to achieving the goals of energy efficiency programs, while adding corporate gains to the companies, such as positive corporate image, business strategy improvement and stakeholders’ engagement. Links between international climate public policy goals, specific governmental EE programs goals, and companies’ behavioral change programs are presented.